STUDIES ON EFFECTIVENESS AND EFFICIENCY OF GAMMA RAYS IN BLACK GRAM ( CK GRAM (Vigna mungo igna mungo (L.) HEPPER) .) HEPPER) - M. DHASARATHAN; S. GEETHA; N. MEENAKSHIGANESAN (The Bioscan, 2018)
The study was undertaken to assess the effectiveness and efficiency of gamma rays on three different varieties of black gram. Genetically pure, uniform and dry seeds of black gram varieties viz., ADT 3, CO 6 and TU 17-9 were treated with four different doses (200, 300, 400, and 500 Gy) of gamma rays. The biological damage based on lethality, injury and sterility were estimated in the M1 generation. Both chlorophyll and morphological mutations were studied in the M2 generation to calculate the effectiveness and efficiency of gamma rays based on biological damage in M1. Differential response of varieties and varied doses of mutagenic treatment in induction of macromutation in M2 generation was observed among the varieties. The degree of effectiveness and efficiency varied among different mutagenic doses and the varieties. Higher degree of effectiveness and efficiency at lower and intermediate doses of mutagen and optimum dose was found at 200 Gy, were observed among three varieties which may be due to less biological damage.